Algorithmic Objectivity as Ideology: Toward a Critical Ethics of Digital Capitalism. - De Ruvo, Giuseppe (Topoi: An International Review of Philosophy, 2025)
After reviewing various informal definitions, the article shows how algorithms' implementation still presents clear limitations, despite Big Tech's enthusiastic narratives. We then show the ideological nature of the concept of algorithmic objectivity, developing a practical account of ideology. We argue that, along with other devices, algorithmic objectivity imbues subjects with a structural reflexivity deficit, by virtue of which Big Tech's power practices are not perceived as such. In its conclusion, the article argues for a critical ethics for the digital age, capable of taking into account the power dynamics that run through it.